PENGGUNAAN HEATER SEBAGAI ALTERNATIF EFEKTIF UNTUK PEMANAS PADA MESIN PENGERING IKAN DAN KERUPUK - Borrong, Raya Hidayat; Arifin, Zainal; Afma, Vera Methalina (PROFISIENSI : Jurnal Program Studi Teknik Industri, 2024)
ABSTRACT This research aims to determine the effectiveness of using a heater as an alternative heater in fish and cracker drying machines. Conventional heating that uses sunlight or fossil fuels is often inefficient and inconsistent in producing the desired product quality. In this study, electric heaters were tested as the main heat source to overcome this problem. The experimental method was carried out by measuring drying time, energy consumption, and final product quality such as air content, texture, and nutritional value. The research results show that the use of a heater can reduce drying time by up to 30% compared to conventional methods. In addition, energy consumption is more efficient with more consistent product results in terms of texture and air content. The quality of the final product also increases with lower and more stable air content, as well as better texture compared to conventional drying. Therefore, the use of a heater as an alternative heater in fish and cracker drying machines can be considered an effective and efficient solution, providing economic benefits and better product quality.